Civil Liability for Mining Companies for Environmental Pollution Based on Indonesian Laws - Sarmilah, Milah; Mustafidah, Lina; George, Hellen (Universitas Negeri Semarang, 2022)
Environmental pollution has a broad legal dimension, in addition to criminal sanctions in various related legal regulations, there are also administrative and civil law aspects. This study aims to analyze how civil sanctions in environmental pollution are carried out by mining companies based on Indonesian legal rules. This study proves and confirms that in principle, every person in charge of a business and/or activity who commits an unlawful act in the form of pollution and/or environmental destruction that causes harm to other people or the environment is obligated to pay compensation and/or take certain actions. In addition to being required to pay compensation, the polluter and/or environmental destroyer may also be burdened by the judge to take certain legal actions, for example an order to install or repair a waste treatment unit so that the waste complies with the specified environmental quality standards; restore environmental functions; and/or eliminate or destroy the causes of environmental pollution and/or destruction.